Morphological characterization of seed-borne fungi associated with BRRI rice varieties in Bangladesh - Sultana, Tania; Bashar, MA; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2020)
Twenty five fungal species, representing 13 genera were found to be associated with seeds of 20 varieties of rice (BRRI dhan 56 to BRRI dhan 75). Fungi were isolated following "Tissue planting" method and "Blotter method". The isolated fungi were Alternaria alternata, A. tenuissima, Aspergillus flavus, A. fumigatus, A. niger, A. ochraceus, A. terreus, Bipolaris multiformis, B. oryzae, B. sorokiniana, Chaetomium globosum, Curvularia lunata, Fusarium equiseti, F. fugikuroi, F. oxysporum, F. proliferatum, Microdochium fisheri, Nigrospora oryzae, Penicillium sp., Pestalotiopsis oxyanthi, Phanerochaete chrysosporium, Rhizopus stolonifer, Sarocladium oryzae, Syncephalastrum racemosum and Trichoderma viride. Dhaka Univ. J. Biol. Sci. 29(1): 75-86, 2020 (January)